THE CONTENTS OF 20-HYDROXYECDYSONE (20E), QUERCETIN AND ESSENTIAL OILS IN ASTERACEAE SPECIES GROWING IN TAM DAO DISTRICT, VINH PHUC PROVINCE, VIETNAM - Ngoc Huyen, Dang; Thi Tuyen, Phung; Thi Loan, Vu; Xuan Dac, Le (Journal of Forestry Science and Technology, 2019)
In this study, 36 species belonging to 23 genera of family Asteraceae were discovered in Dai Dinh commune, Tam Dao district, Vinh Phuc province, of which Vernonia is the most diverse genus with four species accounting for 11.42% out of 36 species. The contents of 20-hydroxyecdysone (20E), quercetin and essential oils were evaluated for Asteraceae species with different plant parts. The results showed that among 36 species, the compound 20E was detected in 11 species, quercetin was found in seven species and essential oils were evaluated in 23 species. The 20E content in the species varied from 0.005 % to 0.245% of dry weight with the highest concentration was presented in Eupatorium fortunei. Artemisia vulgaris contained maximum amount of quercetin with 0.349% of dry weight while Adenostemma viscosum obtained the higher essential oils in the branch and leaf extracts than other speices. From the obtained information, this study could conclude that Eupatorium fortunei, Artemisia vulgaris, and Adenostemma viscosum have high value of 20E, quercetin and essential oils respectively will become potential sources of bioactive ingredients for foods, pharmaceuticals and medicinal products.